The Implementation of the School Literacy Movement to Build Students’ Reading Habits - Fani Hindun Muawanah; Wahyuni, Sri (Universitas Negeri Semarang, 2025)
This research is motivated by the phenomenon of low literacy culture in Indonesian society. The real step to building a reading habit from an early age is a program that can motivate students to read. As a formal learning environment, Madrasah context in Indonesia plays an important role in creating a community of readers. This study aims to determine how the School Literacy Movement (SLM) is implemented at a private primary school called MI Darul Ulum, Wates, Semarang, Indonesia and to determine the students' perceptions of implementing the SLM to build students' reading habits. The study included the school principal, three teachers, and 109 students. The study used a descriptive qualitative design with a case study design. Data was collected using observation, interviews, documentation, and questionnaires. The data analysis method used the stages such as data reduction, data display, and conclusion. The results show that the character of students' reading habits was still low due to being constrained by COVID-19 pandemic for two years. The literacy program was halted so the existing pre-designed literacy activities could not be fully implemented. Moreover, the facilities and infrastructure of the literacy program were damaged because they lacked maintenance. Only SMS (Sabtu Membaca Senyap) or silent reading program and regular school library visits could be executed among the scheduled activities. Based on the results of this study, literacy programs need to be held intensively. There is also a need for innovation or renewal in literacy programs and infrastructure to support the running of the literacy program and improve students' reading habits.